Measurement of Benzo[a]pyrene Concentration in Tobacco Combustion using MQ-6 Gas Sensor - Cantika, Faradisa Aprilicha; Wardoyo, Arinto Yudi Ponco; Putro, Triswantoro; A, Renetha Salma Myesha (Master Program in Mechanical Engineering, Gunadarma University, 2024)
Benzo[a]pyrene is one of the compounds from the Polycyclic Aromatic Hydrocarbons (PAHs) group that is found in various places as a by-product of combustion. In addition, this compound also has carcinogenic properties so it has a bad impact on human health. Therefore, research is needed to detect the presence of benzo[a]pyrene compounds by designing a measurement system for this detection, especially in burning tobacco. The measurement system that has been designed uses a RobotDyn Mega WiFi 2560 microcontroller and an MQ-6 gas sensor that has been calibrated with benzo[a]pyrene compounds. The results showed that the concentration of benzo[a]pyrene detected when burning tobacco at a mass of 0.33 gram was 4.86 ppb, 7.38 ppb for 0.436 grams mass burning, and was 8.81 ppb for burning at a mass of 0.52 grams. Therefore, this measurement system has been able to detect benzo[a]pyrene compounds